Produção e consumo conscientes: o caso da obsolescência planejada - Luna , Arthur Augusto Barbosa (2018)
The present study had as objective to analyse the planned obsolescence, to a better understanding about the effectiveness of the Brazilian laws to fight it. Pursuing this goal, it has been written discussing relevant topics to the theme, such as a brief about the transformation of consume into consumerism and about the history of planned obsolescence, creating a connection between it and the consumerism, as well as detailing the categories uses do characterize it. Having in mind the desire to facilitate the perception on how this practice is carried on, it has been discussed about howmarketing techniques, and how they can be associated planned obsolescence. On the same north, it was presented how operations management can be capable to insert elements that will cause premature and pre-determined obsolescence during the moment the products are manufactured, demonstrating the reason why it is so hard to prove when companies artificially plan obsolescence. From this point, it was detailed the concepts of product flaw according to the Código de Defesa do Consumidor (Consumer Defense Code), so it was possible to explain why planned obsolescence cannot be confused with it, and why the artificial obsolescence does not depend on the existence of flaw in the product to occur. For this reason, it was argued in detail that the protections from CDC are not capable to fight the practice – both the protections that talk about product flaws or the ones that disciplined the offer and publicity –, due to the particularities and subtleties inherent to the way planned obsolescence is carried on. That said, attempts to regulate and prevent its occurrence were listed and detailed, and, in sequence, eventual suggestions to fight it were presented.